Can journalism survive? : an inside look at American newsrooms - Ryfe, David 1966- (Polity Press, 2012)
"Journalists have failed to respond adequately to the challenge of the Internet, with far-reaching consequences for the future of journalism and democracy. This is the compelling argument set forth in this timely new text, drawing on the most extensive ethnographic fieldwork in American newsrooms since the 1970s. David Ryfe argues that journalists are unable or unwilling to innovate for a variety of reasons: in part because habits are sticky and difficult to dislodge; in part because of their strategic calculation that the cost of change far exceeds its benefit; and in part because basic definitions of what journalism is, and what it is for, anchor journalism to tradition even when journalists prefer to change. The result is that journalism is unraveling as an integrated social field; it may never again be a separate and separable activity from the broader practice of producing news. One thing is certain: whatever happens next, it will have dramatic consequences for the role journalism plays in democratic society and perhaps will transform its basic meaning and purpose."--Publisher's website.